(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
“Symbolic Interactionism is a school of thought in sociology that explains social behaviour in terms of how people interact with each other via symbols. This approach was formulated by Blumer (1969). It is the process of interaction in the formulation of meaning for individuals. Symbolic Interactivism is an American theory that develops from Practical considerations and alludes to people’s particular Utilization of dialect to make images, normal implications, for deduction and correspondence with others. In addition, interactionism is the study of how individuals shape society and is shaped by society through meaning that arises in interactions.”